IMPLEMENTASI PELATIHAN MICROSOFT WORD DALAM PENYUSUNAN MAKALAH BAGI SISWA MA NURUL KHOIROH PEKARANGAN KELIR KALIPURO BANYUWANGI - Zaehol Fatah; Nur Aini (Jurnal Padamu Negeri, 2026)
The rapid development of information technology requires students to possess adequate digital competencies, particularly in using Microsoft Word for academic writing. However, students at MA Nurul Khoiroh Pekarangan Kelir Kalipuro Banyuwangi face limited access to technology, resulting in low proficiency in producing properly formatted and systematic academic papers. This study aims to describe the implementation and outcomes of a Microsoft Word training program for students at MA Nurul Khoiroh. The method employed was descriptive qualitative through a community service approach, consisting of three stages: preparation, implementation, and evaluation. The training was conducted using lecture, direct demonstration, and guided practice methods, covering materials such as margin settings, text formatting, heading creation, automatic table of contents, and page numbering. The results indicate a significant improvement in students' abilities, from merely typing plain text to producing well-formatted papers in accordance with academic writing standards. This activity demonstrates that a practical and guided training approach is effective in enhancing the digital literacy of students in rural areas.